Business Analysis Of Broiler Chicken Farm With Partnership System In Limbangan Kendal District - Istanto Istanto; Suprapti Supardi; Sri Wahyuningsih (MEDIAGRO, 2010)
This study entitled " Business Analysis of Broiler Chicken FarmWith Partnership System In Limbangan Kendal District." This study aims toknow how the pattern - pattern of broiler partnership in District Limbanganand how much it costs, revenues, earnings, and profits from farming ofbroiler chickens with partnerships system and feasibility level of businessfarm with partnerships system that can later be used as a reference for thepeople doing business broiler chicken Farm. To know the pattern - patternof broiler partnership in District Limbangan using analysis methodsapproach the existing partnership and to know the feasibility level ofbusiness farm using gross benefit cost ratio (gross B/C), BEP andproductivity costs. Determining the location of this study purposively withthe reasons in the two villages was the most total population of broilers(broiler) are farmed by people in the Region District Limbangan order toproperly represent the village which has a smaller population. For samplingrespondents was conducted using census (census sampling). About 25farmers from a total of 25 farmers that can later be represented inLimbangan Kendal District. The results showed that PIR partnership patternused by breeders because it is very beneficial because these patterns is thecore company as foster father that supplies sapronak, coaching in businessmanagement to marketing. Average area of cage 850.72 m2 with chickenpopulations 7240 tail derived income of Rp. 21,841,960, - and an averageprofit of Rp. 17.365.713,-. Viewed from the BEP business farm of broilerchickens has a value of 8.375 which means that in a population of 8.375farmers benefited and suffered no losses. While the productivity of capitalobtained a value of 13.12% / season, this value is high than the capitalinterest 0,208 /month, so in terms of capital productivity of broiler chickensworth conducting.Keywords: Analysis, Business farm of Broiler Chickens, Feasibility,Partnership.